Isolated Epididymal Tuberculosis : A Case Report - Haque, M Manzurul; Kadir, M Lailatul; Badruddoza, SM; Islam, Zahidul; Kamal, AHM Mostofa (TAJ: Journal of Teachers Association, 2018)
Isolated tubercular epididymitis is not a very common pathological entity. Tuberculosis of the epididymis is usually associated with infection of the ipselateral testis. More over it usually presented in early adult age group. Here we are communicating an isolated right epididymal tuberculosis in a sixty eight years old man. The diagnosis was suspected on clinical examination and ultrasonogram scanning of the testes and epididymis, was supported by FNAC study of the scrotal swelling and was confirmed by histopathological examination of excised lump following surgical exploration. TAJ 2014; 27(1): 64-66